A computerized test for the assessment of mild cognitive impairment subtypes in sentence processing. Issue 6 (2nd November 2018) - Segkouli, Sofia; Paliokas, Ioannis; Tzovaras, Dimitrios; Lazarou, Ioulietta; Karagiannidis, Charalampos; Vlachos, Filippos; Tsolaki, Magda
ABSTRACT: This study examines thesentence processing ability of mild cognitive impairment (MCI) subtypes. In addition to standard MCI neuropsychological tests, an experimental approach was applied to assess language. 133 people (93 MCI/40 controls) participated in novel computerized sentence processing tasks. Results presented statistically significant differences between MCI/controls andMCI subtypes (ANOVA):(a) duration F(2, 92) = 19.259, p  < .001) in sentence construction; (b) correct answers (F(2, 89) = 8.560, p  < .001) and duration (F2, 89) = 15.525, p  < .001)in text comprehension; (c) correct answers (F(2, 92) = 8.975, p  < .001) andduration (F(2, 92) = 4.360, p  = .016) in metaphoric sentences comprehension; (d) correct answers (F(2, 92) = 12.836, p  < .001) andduration (F(2, 92) = 10.974, p  < .001) in verb form generation. Subtle changes in MCIsubtypes could affect sentence processing and provide useful information for cognitive decline risk estimation and screening purposes.